Mycobacterium tuberculosis var. tuberculosis infection in two captive black capuchins (Sapajus nigritus) in Southern Brazil - Ehlers, Luiza Presser (Braz J Microbiol, 2020)
Tuberculosis is a common zooanthroponosis in humans with a high incidence in Brazil, but it may also affect non-human primates (NHPs), of which Old World primates are most commonly involved. Nonetheless, its occurrence in New World primates is unknown, and therefore, this study aimed to describe the infection by Mycobacterium tuberculosis variant tuberculosis in two captive black capuchin monkeys (Sapajus nigritus) in Southern Brazil. The primates were housed in the same enclosure, wherein close contact with humans frequently occurred, and presented apathy, anorexia, and death in a clinical course of 15 days to 2 months. At the necropsy, the tracheobronchial lymph nodes were markedly enlarged and firm to hard and on the cut surface had a caseous aspect. The lungs exhibited two injury patterns: multifocal and disseminated. Microscopically, the lungs exhibited multifocal to coalescing necrotic granulomas and non-necrotic granulomas, with multiple acid-fast bacilli within the cytoplasm of epithelioid macrophages and multinucleated giant cells. Bacilli were also labeled upon immunohistochemistry (IHC) for Mycobacterium tuberculosis. Microbiological culture of lung samples from both cases yielded colonies compatible with M. tuberculosis. The isolates were identified as M. tuberculosis var. tuberculosis through polymerase chain reaction (PCR). Although tuberculosis is poorly described in New World primates, M. tuberculosis var. tuberculosis may cause a highly contagious and progressive disease with high mortality in black capuchin monkeys (S. nigritus).